Recent Progress in Electrospun Nanofibres: Reinforcement Effect and Mechanical Performance - Mohammadzadehmoghadam, Soheila; Dong, Yu; Davies, Ian (John Wiley and Sons Inc, 2015)
Composite materials are becoming increasingly important as structural materials for aeronautical and space engineering, naval, automotive, and civil engineering, sporting goods, and other consumer products. Fiber-based reinforcement represents one of the most effective manufacturing strategies for enhancing the mechanical strength and other properties of composite materials. Electrospinning has gained widespread interest in the last two decades because of its ability to fabricate continuous ultrafine nanofibers with unique characteristics. The impact of electrospinning on fiber synthesis and processing, characterization, and applications in drug delivery, nanofiltration, tissue scaffolding, and electronics has been extensively studied in the past. In this article, the authors have focused on a comprehensive review of the mechanical performance and properties of electrospun nanofibers as potential reinforcements as well as their advanced nanocomposites.